Orphan eleven - Choldenko, Gennifer, 1957- (Wendy Lamb Books, 2020)
In 1939, after cruel treatment at her orphanage renders her mute, Lucy runs away and joins the circus, working with the elephants and unaware that the orphanage matrons are hunting for her.